EVOLUSI RELEVANSI ETIKA BISNIS DAN CORPORATE SOCIAL RESPONSIBILITY (CSR) - Fanny Dewi Sukma; Iriani Ismail (JURNAL LENTERA BISNIS, 2023)
This research aims to describe and analyze the evolution of the relationship between business ethics and Corporate Social Responsibility (CSR) and its impact on modern corporate business practices. The method used is a literature review with data collection from reputable journal databases such as Scopus, Google Scholar, and ScienceDirect and then selected based on topic relevance and methodological quality. The data obtained was analyzed qualitatively to identify concepts related to the relationship between business ethics and CSR, look at existing empirical studies, and summarize relevant findings. The results show that there is a paradigm shift from separate social responsibility to full integration of business ethics and sustainability in core corporate strategies. This is driven by global factors and rising stakeholder expectations. The global implications of this research are that it provides guidance and insights for companies in developing CSR policies that are more effective and responsive to social and environmental issues, as well as enhancing corporate social responsibility globally. This research provides an accurate and well-established picture of the relationship between business ethics and CSR in the current context and can serve as a strong foundation for sustainable and responsible business decision-making. Keywords: Corporate Social Responsibility, Business Ethics, Sustainability, Evolution